Non-communicable disease multimorbidity among tribal older adults in India: evidence from Study on Global AGEing and adult health, 2015 - Sinha, Abhinav; Kanungo, Srikanta; Bhattacharya, Debdutta; Kaur, Harpreet; Pati, Sanghamitra (Frontiers in Public Health, 2023)
Multimorbidity defined as the simultaneous presence of two or more chronic conditions in an individual is on the rise among low-and middle-income countries such as India. With India aiming to achieve Universal Health Coverage, it is imperative to address the inequalities in accessing healthcare especially among vulnerable groups such as tribal. Moreover, changing lifestyle has led to emergence of multimorbidity among tribal in India. We aimed to estimate the prevalence and assess the correlates of multimorbidity among tribal older adults in India.We employed a nationally representative data from the World Health Organization's Study on Global AGEing and Adult Health conducted in 2015. We included 522 participants aged ≥50 years who reported their caste to be 'Scheduled Tribe' in the survey. A multivariable regression model assessed the association between multimorbidity and various attributes.Arthritis, cataract and hypertension were the most common chronic conditions. The overall prevalence of multimorbidity was around 22.61%. We observed a higher likelihood of having multimorbidity among respondents aged ≥80 years ] than the younger age groups, and among the most affluent group [AOR: 2.64 (1.06-6.56)] than the most deprived class.The prevalence of multimorbidity among tribal older adults is emerging which cannot be overlooked. Health and Wellness Centres may be a window of opportunity to provide egalitarian